Biomass as a source of adsorbents for CO2 capture - Karimi, Mohsen (2022)
CO2 capture and global warming have become the major anxiety of mankind in recent decades, and many researchers attempt to find the best strategies for these challenges. Besides the nature of global warming, the rapid increase of population and high consumption of energy have intensified this problem.